Determination of Physicochemical Properties and Fatty Acid Composition of Khella (Ammi visnaga L.) Seeds Oil using Gas Chromatography-Mass Spectrometry - A. Noraldaum, Hadeel; O. Babikir, Mohammed; Mohamed, Yasmin Ali (Gezira Journal of Engineering and Applied Sciences, 2023)
Ammi visnaga L. (Family Umbelliferae), also known as Khella Baldi or toothpick weed, is an annual  herb indigenous to the  Mediterranean region of North Africa, Asia, and Europe. The plant is known to have been used in traditional medicine a long time ago. Nowadays, it is used in modern medicine to treat many aliments such as renal colic and coronary insufficiency, and is used as an antioxidant, antifungal, and antibacterial, with a larvicidal effect on mosquito larvae. The aim of this work is to determine fatty acid composition and physio-chemical properties of oil extracted from the seeds of Ammi visnaga L. Amount of 75 g clean seeds were crushed and the oil was extracted by soxhlet using n-hexane as a solvent. The fixed oil from Ammi visnaga seeds oil  was analyzed by gas chromatography coupled with mass spectrometer. The results obtained contain saturated as well as unsaturated fatty acids of A. visnaga seeds oil. From GC-MS analysis the main constituents of fatty  acid oil  were Betroselinic acid  (62.01%) , Linoleic acid (8.9%),  Palmitic acid (6.61%) and butyric acid  (1.94%). The physio-chemical analyses of Ammi visnaga seeds oil were also measured according to the American Oil Chemists  Society (AOCS) official methods,2003.  Results showed that the percentage yield of the oil was 8.6% and the color of the oil was dark green. The density, moisture content and refractive index were 1.44 g/ml ,4.77%, 1.49 respectively. The acid value,  saponification number, free fatty acids and peroxide values were in the order 9.61mgKOHg-1, 154.11mgKOHg-1, 6.768mgKOHg-1, 23.022 meqKg-1 respectively. The results revealed that Ammi visnaga oil  can be used in cosmetic and pharmaceutical industries. The study  recommend to use different solvents to extract oil from the seeds of Ammi visnaga L. and compare their result. Also study the effect of Ammi visnaga oil  on microorganisms.